Strategies Of India As A Pioneer Investor - S. Rajendran (International Marine Minerals Society, 2003)
India?s interest in the resources of the deep seabed particularly the manganese nodules in the Indian Ocean can be traced back to the Indian Ocean Expedition of 1960 ? 65. The collection of Manganese Nodule samples from the Indian Ocean in January 1981 aroused considerable interest within the scientific community. Following several surveying expeditions, the Central Indian Ocean was identified as the most promising area for exploitation. India was accorded ?Pioneer Investor? status and further research and development programs were launched to establish the techno-economic viability of deep seabed mining. India has also shown considerable progress in the field of development and testing of methods for processing the nodules. The Department of Ocean Development manages the program.